Regional Ethnic and Confessional Situation in the Russian Federation: Arrangements for Monitoring - A. N. Sadovoy; V. A. Ovchinnikov (Вестник Кемеровского государственного университета, 2021)
The article introduces new methodological foundations for analyzing the current ethno-social and ethno-confessional situation in various constituents of the Russian Federation, namely an ethno-social and confessional monitoring based on systematic, selective, and process approaches. Modern ethnic and confessional processes manifest the transformation of traditional social institutions and communications in traditional economy and social organization as a result of state policy. The structural and functional method made it possible to identify the historical context of the impact that religious organizations produce on traditional social institutions. The authors tested a systematic approach to the analysis of the ethnosocial and ethno-confessional situation on three levels: 1) interstate (macro) level in the transboundary zones of southern Russia), 2) regional (mega) level of the fractal and network social organization, 3) micro level within the boundaries of sample polygons. The article also focuses on the problems of secondary analysis of historiographical sources about the history of state national and confessional politics in the XIX – early XXI centuries. It introduces basic definitions used in regional ethno-social monitoring. The topic needs further integrated and applied research.